Intra- and inter-specific cortisol coregulation - CHARLOTTE SOLMAN (2023)
Coregulation is the bidirectional modulation of social partners’ physiology, including hypothalamic-pituitary-adrenal (HPA) axis activity, and it is key for forming and maintaining attachment bonds between individuals. By investigating coregulation of acute and chronic cortisol in dog-human, dog-dog, and human-human dyads, this thesis aims to further our understanding of social and temporal drivers of coregulation and their potential links to attachment. Chapter 1 outlines how coregulation regulates attachment bonds and reviews existing cortisol coregulation literature in parent-infant and spousal dyads, non-human dyads, and human-non-human dyads. In Chapter 2, I describe the methodology used across Chapters 3-6. Chapter 3 explores whether factors commonly associated with stronger coregulation in parent-infant dyads also predict dog-owner coregulation strength. Chapter 4 tests for coregulation in cohabiting dogs, and demonstrates that the absence of the owner (i.e. an external social influence) may strengthen dog-dog cortisol coregulation. Chapter 5 explores how chronic cortisol concentrations (derived from hair) may enhance the study of coregulation, and presents preliminary evidence suggesting that the predictors of coregulation strength depend on the temporal nature of the cortisol measure utilised (i.e. acute or chronic cortisol concentrations). Chapter 6 highlights how greater dyad similarity in Big-5 personality traits may strengthen romantic couples’ coregulation – an area that has received minimal attention in the literature. Lastly, in the general discussion (Chapter 7), I place the key findings in a wider context and outline potential implications for future studies. Overall, results from Chapters 3-6 further our knowledge of cortisol coregulation and indicate that the physiological mechanism has shared characteristics across types of social relationships and species. Additionally, I show how external social influences and inter-individual differences in personality have the potential to be key predictors of coregulation strength, which could have considerable implications for the methodologies of future coregulation studies (provided these findings persist in a larger sample).